Tahap kesedaran pekerja pembinaan terhadap keselamatan dan kesihatan pekerjaan: Kajian di tapak pembinaan SA2 Logistic Hub - Md Fadlie, Abdul Rani (2016)
This paper is aim to examine the level of occupational safety and health awareness of construction workers at SA2 Logistic Hub construction site. SA2 Logistic Hub construction site is chosen for this study because their workers are exposed to risk and safety and health hazards. One dependent variable was chosen namely level of occupational safety and health awareness and three independent variables, namely, commitment of workers to safety and health at workplace, function of safety and health committee at the workplace and occupational safety and health training at workplace have been identified. A questionnaire was used as research instrument and the data were analyzed using Statistical Package for Social Sciences (SPSS). The results of this study found that construction workers on a construction site SA2 Logistic Hub have a high level of awareness of occupational safety and health and all three variables have a significant influence on the level of occupational safety and health awareness. The comparison between these three variables resulted occupational safety and health training at workplace is the most dominant variables affecting the level of occupational safety and health awareness among construction workers at SA2 Logistic Hub construction site.